2021
DOI: 10.1186/s13048-020-00746-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dietary micronutrient intake in PCOS patients with and without metabolic syndrome

Abstract: Background Polycystic ovarian syndrome (PCOS) is the most common endocrine disorder in reproductive-age women. It is one of the risk factors of metabolic syndrome (MetS). These two syndromes have an inflammatory etiologic foundation along with oxidative stress. The present study aimed to compare the dietary intake of antioxidant micronutrients in PCOS women with and without MetS. Materials and methods Overall, 42 participants eligible for this nest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
(80 reference statements)
0
11
0
Order By: Relevance
“…Thereafter, 6 additional studies were acquired from the reference lists for the retrieved articles. Eventually, a total of 25 studies were selected for this meta-analysis ( 17 – 41 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thereafter, 6 additional studies were acquired from the reference lists for the retrieved articles. Eventually, a total of 25 studies were selected for this meta-analysis ( 17 – 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…These studies were published between 2003 and 2021. Among which, 14 studies were performed in Asian countries [Korea (18,19,21,(35)(36)(37)(38)(39), China (29,30,33,40), Iran (31,41) and Saudi Arabia (28)], and 4 ones were conducted in European countries [Poland (34,38), France (20) and Finland (24)]. The other 7 studies were from US (17,23,25,26,32), Brazil (22) and Nigeria (27).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…2021 [17] Nested case control study The dietary intake of the micronutrients including vitamin E could probably have a protective effect on metabolic syndrome. 2021 [18] Pilot randomized, placebocontrolled trial 8 weeks of vitamin E supplementation in women with PCOS showed positive effects on body weight, Ang-1/Ang-2 ratio, Ang-1, and vascular endothelial growth factor (VEGF) level. Monocentral, randomized, controlled, double-blinded trial A minimum of 3 months of micronutrients supplementation including vitamin E showed benefits in women with PCOS.…”
Section: Vitamin E and Pcos -Summary Of Clinical Trials Reportsmentioning
confidence: 99%